LΩUI: Lovely ΩMEGA User Interface - Siekmann, Jörg; Hess, Stephan; Benzmüller, Christoph; Cheikhrouhou, Lassaad; Fiedler, Armin; Horacek, Helmut; Kohlhase, Michael; Konrad, Karsten; Meier, Andreas; Melis, Erica; Pollet, Martin; Sorge, Volker (Formal aspects of computing, 1999)
The capabilities of a automated theorem prover's interface are essential for the effective use of (interactive) proof systems. L Ω UI is the multi-modal interface that combines several features: a graphical display of information in a proof graph, a selective term browser with hypertext facilities, proof and proof plan presentation in natural language, and an editor for adding and maintaining the knowledge base. L Ω UI is realized in an agent-based client-server architecture and implemented in the concurrent constraint programming language Oz.